Comparative metabolomics and glycolysis enzyme profiling of embryogenic and nonembryogenic grape cells. Issue 5 (17th April 2018) - Parrilla, Jonathan; Gaillard, Cécile; Verbeke, Jérémy; Maucourt, Mickaël; Aleksandrov, Radoslav A.; Thibault, Florence; Fleurat‐Lessard, Pierrette; Gibon, Yves; Rolin, Dominique; Atanassova, Rossitza
Abstract : A novel biological model was created for the comparison of grapevine embryogenic cells (EC) and nonembryogenic cells (NEC) sharing a common genetic background but distinct phenotypes, when cultured on their respective most appropriate media. Cytological characterization, 1 H‐NMR analysis of intracellular metabolites, and glycolytic enzyme activities provided evidence for the marked metabolic differences between EC and NEC. The EC were characterized by a moderate and organized cell proliferation, coupled with a low flux through glycolysis, high capacity of phosphoenolpyruvate carboxylase and glucokinase, and high oxygen consumption. The NEC displayed strong anarchic growth, and their high rate of glycolysis due to the low energetic efficiency of the fermentative metabolism is confirmed by increased enolase capacity and low oxygen consumption. Abstract : The comparison of grape embryogenic cells (EC) and nonembryogenic (NEC) cells sharing a common genotype and cultured on their appropriate media shows two independent phenotypes with specific cell fate determination. The comparative analysis of cytological characteristics, growth kinetics, cellular metabolites, and glycolysis enzymes of grape EC and NEC revealed marked differences in their proliferation, metabolic behavior, and glycolytic metabolism.